Improving Student Learning Outcomes in Mathematics Learning through a Contextual Teaching and Learning Approach in Elementary Schools - Misqa, Laina; Oviana, Wati; Hayati, Zikra; Jannah, Misbahul (MANDAILING GLOBAL EDUKASIA, 2024)
Learning mathematics is one of the lessons that must be mastered by students. To a certain extent, mathematics can help students overcome various problems in everyday life. This research aims to improve student learning outcomes in mathematics learning by applying the Contextual Teaching and Learning approach. This research is classroom action research. The subjects in the research were students of class V-3 MIN 7 in Banda Aceh City, totaling 49 students. Data collection techniques were carried out using observation and test techniques. The data obtained was then analyzed using descriptive statistical techniques. Learning outcome data is analyzed based on the standard value set, namely 80 with classical completeness of 90%. The results showed that teacher activity in the first cycle increased to 75% in the good category. Furthermore, in the second cycle, it was 84.37% in the very good category, and increased again in the third cycle, namely to 94.79% in the very good category. Meanwhile, student activity in the first cycle was 71.87% in the good category, in the second cycle it increased to 82.29% in the very good category, and increased again in the third cycle to 92.70% in the very good category. The increase in learning outcomes in the first cycle was 65.3% in the sufficient category. Then it increased in the second cycle to 81.63% in the very good category, and increased again in the third cycle to 93.87% in the very good category. So it can be concluded that the application of the Contextual Teaching and Learning approach can increase teacher activity, student activity and student learning outcomes in class V MIN 7 Banda Aceh City.